2011
DOI: 10.1590/s0037-86822011000600010
|View full text |Cite
|
Sign up to set email alerts
|

Study on Chagas disease occurrence in the municipality of Monte Negro, State of Rondônia, Brazilian Amazon

Abstract: Introduction: Studies on Chagas disease deal with the perspective of its occurrence in the Amazon region, which is directly correlated to the population growth and the spread of the bug biotope. The state of Rondônia has an immense source of vectors (Triatomine) and reservoirs of Trypanosoma cruzi. Environmental changes brought forth by the deforestation in the region may cause vector behavior changes and bring these vectors to a closer contact with humans, increasing the probability of vector infection. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Of 4895 articles identified, 42 were considered eligible for the review (Aras et al, 2002;Arruda et al, 1984;Bento et al, 1984;Bento et al, 1989;Bento et al, 1992;Bezerra et al, 1983;Boia et al, 1999;Borges-Pereira et al, 2001;Borges-Pereira et al, 2006;Borges-Pereira et al, 2008;Brito et al, 2012;Carvalho et al, 2011a;Carvalho et al, 2003;Carvalho et al, 2011b;Coimbra et al, 1992;Corrêa et al, 2011;Coura et al, 1995a;Coura et al, 1995b;Coura et al, 2002;Dantas-Maia et al, 2007;Dias et al, 2002a;Diotaiuti et al, 2000;Escolano et al, 1989;Figueredo-Silva et al, 1991;Fonsêca et al, 2012;Gazin et al, 2004;Lima et al, 2012;Luitgards-Moura et al, 2005;Machado et al, 1998;Magalhães et al, 2011;Massaro et al, 2008;Montoya et al, 2003;Passos et al, 1997; Peñaranda-Carrillo et Pereira and Coura, 1986;Pereira and Coura, 1987;Silva et al, 2009;Silva et al, 2010;Silva and Goldenberg, 2008;Tachibana et al, 1999;Valente et al, 1998) (Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Of 4895 articles identified, 42 were considered eligible for the review (Aras et al, 2002;Arruda et al, 1984;Bento et al, 1984;Bento et al, 1989;Bento et al, 1992;Bezerra et al, 1983;Boia et al, 1999;Borges-Pereira et al, 2001;Borges-Pereira et al, 2006;Borges-Pereira et al, 2008;Brito et al, 2012;Carvalho et al, 2011a;Carvalho et al, 2003;Carvalho et al, 2011b;Coimbra et al, 1992;Corrêa et al, 2011;Coura et al, 1995a;Coura et al, 1995b;Coura et al, 2002;Dantas-Maia et al, 2007;Dias et al, 2002a;Diotaiuti et al, 2000;Escolano et al, 1989;Figueredo-Silva et al, 1991;Fonsêca et al, 2012;Gazin et al, 2004;Lima et al, 2012;Luitgards-Moura et al, 2005;Machado et al, 1998;Magalhães et al, 2011;Massaro et al, 2008;Montoya et al, 2003;Passos et al, 1997; Peñaranda-Carrillo et Pereira and Coura, 1986;Pereira and Coura, 1987;Silva et al, 2009;Silva et al, 2010;Silva and Goldenberg, 2008;Tachibana et al, 1999;Valente et al, 1998) (Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Carvalho et al 27 observed a low invasion of triatomine in homes and a pattern of rural properties in Monte Negro, Rondônia, which do not favor the domiciliation of triatomine. In this municipality, the houses are mostly made of concrete and roofs are made of tiles, including henhouses and other deposits; in the same study, a large amount of triatomine were found in Orbygnia speciosa (Babaçu) palm trees, which mostly grow in pasture areas.…”
Section: Discussionmentioning
confidence: 97%